MCNPX Estimation of Photoneutron Dose to Eye Voxel Anthropomorphic Phantom From 18 MV Linear Accelerator - Ali AA Alghamdi (SAGE Publishing, 2023)
The dose due to photoneutron contamination outside the field of irradiation can be significant when using high-energy linear accelerators. The eye is a radiation-sensitive organ, and this risk increases when high linear energy transfer neutron radiation is involved. This study aimed to provide a fast method to estimate photoneutron dose to the eye during radiotherapy. A typical high-energy linear accelerator operating at 18 MV was simulated using the Monte Carlo N-Particle Transport Code System extended version (MCNPX 2.5.0). The latest International Atomic Energy Agency photonuclear data library release was integrated into the code, accounting for the most known elements and isotopes used in typical linear accelerator construction. The photoneutron flux from a 5 × 5 cm 2 field size was scored at the treatment table plane and used as a new source for estimating the absorbed dose in a high-resolution eye voxel anthropomorphic phantom. In addition, common shielding media were tested to reduce the photoneutron dose to the eye using common shielding materials. Introducing a 2 cm thickness of common neutron shielding medium reduced the total dose received in the eye voxel anthropomorphic phantom by 54%. In conclusion, individualized treatment based on photoneutron dose assessment is essential to better estimate the secondary dose inside or outside the field of irradiation.